4
$\begingroup$

Evaluate $$\sum_{n=1}^\infty \frac{n}{2^n}$$

My Work:

$$\sum_{n=1}^\infty \frac{n}{2^n} = \sum_{n=1}^\infty n \left(\frac{1}{2}\right)^n$$

If we denote $f(x) = \sum_{n=1}^\infty nx^n$ then we wish to evaluate $f(1/2)$.

Now, $$\sum_{n=1}^\infty nx^n = x \sum_{n=1}^\infty nx^{n-1} = x\sum_{n=1}^\infty (x^n)' = x\left(\sum_{n=1}^\infty x^n\right)' = x \left(\frac{-x}{1-x}\right)' = \frac{-x}{(1-x)^2}$$

Applying $x=1/2$ we get the wrong result of $-2$.

Where is my mistake?

$\endgroup$

2 Answers 2

5
$\begingroup$

The mistake was in the fourth step -- the $-x$ in $\left(\frac{-x}{1 - x}\right)^{'}$ should be $x$. So you should have

$$\sum_{n = 1}^\infty nx^n = \frac{x}{(1 - x)^2}.$$

$\endgroup$
3
  • $\begingroup$ But $$\sum_{n=1}^\infty x^n = \frac{-x}{1-x}$$ $\endgroup$
    – AlonAlon
    Mar 3, 2015 at 16:40
  • 2
    $\begingroup$ @AlonAlon no, it's $\sum_{n = 1}^\infty x^n = \frac{x}{1 - x}$. $\endgroup$
    – kobe
    Mar 3, 2015 at 16:41
  • 1
    $\begingroup$ It's because $$(1 - x)\sum_{n = 1}^N x^n = \sum_{n = 1}^N (x^n - x^{n+1}) = x - x^{N+1} \to x$$ which implies $$(1 - x)\sum_{n = 1}^\infty x^n = x$$ or $$\sum_{n = 1}^\infty x^n = \frac{x}{1 - x}$$ $\endgroup$
    – kobe
    Mar 3, 2015 at 16:44
2
$\begingroup$

Yet another solution (maybe less tricky).

You can express this as a double summation and exchange the order (this is directly related to the integration by parts): \begin{align} \sum_{n=1}^\infty \frac{n}{2^n} &= \sum_{n=1}^\infty \sum_{k=1}^n \frac{1}{2^n}\\ & = \sum_{n=1}^\infty \sum_{k=1}^\infty \frac{1}{2^n} 1_{k \leq n}\\ & = \sum_{k=1}^\infty \sum_{n=1}^\infty \frac{1}{2^n} 1_{k \leq n}\\ & = \sum_{k=1}^\infty \sum_{n=k}^\infty \frac{1}{2^n}\\ & = \sum_{k=1}^\infty \frac{1}{2^k}\frac{1}{1-\frac{1}{2}}\\ & = 2\sum_{k=1}^\infty \frac{1}{2^k}\\ & = 2. \end{align}

$\endgroup$
2
  • $\begingroup$ What $1_{k\le n}$ is? $\endgroup$
    – AlonAlon
    Mar 3, 2015 at 16:46
  • 1
    $\begingroup$ This is just a notation $1_{k \leq n} = \begin{cases}1 & \text{if }k\leq n\\0 & \text{otherwise}\end{cases}$. $\endgroup$
    – Siméon
    Mar 3, 2015 at 16:47

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.